Quantification of the effect of compression garments on fatigue behavior in cycling - Bajelani, K.; Arshi, A. R.; Akhavan, A. N. (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
Effectiveness of compression garments to enhance athletic performance is the subject of numerous qualitative studies. This study aims at quantification of the effect of compression garments using nonlinear dynamics approach. Kinematic data of fifteen healthy male athletes was obtained and the state space was reconstructed. The trajectory drifts caused by fatigue in the state space were quantified using local flow variation technique. The study illustrates that compression garments (CGs) decrease rate of fatigue development and the body exhibits a more restricted complexity (more predictable and smaller fluctuations) when CGs are worn.